DNA origami-based nano-vaccines for cancer immunotherapy - Tanvir Ahmed (Nano Trends)
Advancements in cancer immunotherapy have been notable; however, challenges remain regarding precision and the capacity to generate robust immune responses. This review explores the potential of DNA origami, an innovative method for structuring DNA into complex forms, as a platform for advanced cancer vaccines. DNA origami enables precise control over the molecular arrangement on its surface. Researchers can precisely modulate the immune response by conjugating tumor-specific antigens and adjuvants to DNA origami nanocarriers. This targeted approach demonstrates significant promise in overcoming the shortcomings of existing immunotherapies. This may enhance vaccine efficacy by facilitating the efficient delivery of antigens and adjuvants to immune cells. The precise control of adjuvant placement can minimize unnecessary immune stimulation and reduce unwanted side effects. The modular structure of DNA origami facilitates the development of personalized vaccines aimed at targeting specific mutations present in a patient's tumor. This advancement offers significant potential for bringing in a new era of precise cancer therapy. DNA origami nanocarriers demonstrate significant potential in enhancing the safety, efficacy, and precision of cancer immunotherapies.